2007
DOI: 10.1246/bcsj.80.2406
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Trifluoromethylation of Ketones with (Trifluoromethyl)trimethylsilane Catalyzed by Chiral Quaternary Ammonium Phenoxides

Abstract: Chiral quaternary ammonium phenoxides were prepared readily from commercially available cinchona alkaloids and employed as novel useful asymmetric organocatalysts. Among these chiral quaternary ammonium phenoxides, a cinchonidine-derived phenoxide that possesses a sterically hindered N(1)-3,5-bis[3,5-bis(trifluoromethyl)phenyl]benzyl group was the most effective for asymmetric trifluoromethylation. In the presence of a catalytic amount of Lewis bases, such as cinchonidine-derived quaternary ammonium phenoxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In this respect, an anionic molecule could function as a potentially more nucleophilic catalyst for initiating the reaction, compared to the commonly utilized electronically neutral molecules, but it generates a rather stable intermediate bearing no charge (see below). [6] Acyl transfer reactions by means of nucleophilic catalysts are the fundamental molecular transformation in synthetic organic chemistry. [2,3] We recently introduced the chiral ammonium betaine 1 as a new, yet intriguing structural motif as an organic molecular catalyst.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, an anionic molecule could function as a potentially more nucleophilic catalyst for initiating the reaction, compared to the commonly utilized electronically neutral molecules, but it generates a rather stable intermediate bearing no charge (see below). [6] Acyl transfer reactions by means of nucleophilic catalysts are the fundamental molecular transformation in synthetic organic chemistry. [2,3] We recently introduced the chiral ammonium betaine 1 as a new, yet intriguing structural motif as an organic molecular catalyst.…”
mentioning
confidence: 99%
“…[6] Acyl transfer reactions by means of nucleophilic catalysts are the fundamental molecular transformation in synthetic organic chemistry. Given that the aryloxylate functionality has a nucleophilic character, we envisioned that 1 could be evolved into a chiral nucleophile after appropriate structural manipulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been made in the development of asymmetric trifluoromethylation reactions [56][57][58][59][60][61][62]. However, the direct enantioselective trifluoromethylation reaction remains a challenge as recently observed when chiral crown ethers were used to the enantioselective trifluoromethylation of aldehydes and ketones [62].…”
Section: Methods Using the Organosilicon Reagent: Tmscfmentioning
confidence: 99%
“…Mukaiyama et al developed a cinchona alkaloid derivative 59 with phenoxide as counteranion (Scheme 27) 53 based on the fact that metal alkoxides are efficient nucleophilic initiators of the Ruppert-Prakash reagent 1. Therefore, they demonstrated that this cinchonidinederived quaternary ammonium phenoxide 59 could catalyze the asymmetric trifluoromethylation of ketones and with 1 efficiently, affording the desired products in high yields and with up to 87% ee (Scheme 27, Table 3, entries 1-11).…”
Section: Scheme 19mentioning
confidence: 99%